Advances in fire safety engineering : selected papers from the 5th Iberian-Latin-American Congress on Fire Safety, CILASCI 5, July 15-17, 2019, Porto, Portugal /: selected papers from the 5th Iberian-Latin-American Congress on Fire Safety, CILASCI 5, July 15-17, 2019, Porto, Portugal. ([2020]) - Unknown
No abstract available